A two-stage laser surgery for fibroplastic changes of the vitreous humor (Ukrainian Journal of Ophthalmology, 2026)
Background. Patients with profilerative vitreoretinopathy are performed vitrectomy which, however, is challenging in the presence of high visual function, transparent lenses, and single vitreoretinal adhesion bands as well as at risk of hemorrhages.Purpose. To determine the efficacy of a two-stage laser treatment, including laser photocoagulation (LP) and laser vitreolysis (LV), for vitreoretinal adhesion bands.Material and Methods. A total of forty-two patients (42 eyes) with fibroplastic changes were treated. Laser interventions were performed in two stages: 1) laser photocoagulation of the retina, in sites where the bands attached the retina, followed by 2) neodymium-doped yttrium aluminum garnet (Nd:YAG) laser vitreolysis. Accurate focusing and adjusting the optimal laser energy contribute to increased treatment efficacy.Results. At the first stage, 36 patients (86%) were performed preventive LP of newly-formed vessels of the bands and limiting LP in the sites of attachment of the bands and membranes. LP was made in the basement of the vitreoretinal bands in the sites where tractional retinal detachment could occur.  At 2-3 weeks, after chorioretinal comissura had been formed, Nd:YAG LV was performed. On treatment completion, visual acuity increased by 27% in 28 patients (67%). In addition, the level of intraocular pressure almost did not change (20.0 mm Hg).The present treatment managed to dissect the vitreoretinal adhesion bands and to decrease a degree of traction in 38 patients (67%).Conclusion. The studies showed a high efficacy of a two-stage laser treatment for vitreoretinal adhesion bands which, in certain cases, can be alternative to surgical treatment, vitrectomy and endolaser photocoagulation.
Keywords: proliferative vitreoretinopathy; laser photocoagulation; Nd-Yag laser vitreolysis